(untitled) (Global Journal of Human-Social Science, 2017)
This paper analyzed macroeconomic fluctuations and economic growth in Nigeria between 1986 and 2014. The paper employed the Atheoretical Statistical Method of Analysis using cross correlations to examine the co-movement between key macroeconomic variables such as broad money supply, oil price, government expenditure, inflation, interest rate, exchange rate and general household consumption and real gross domestic product in Nigeria. Quarterly time series data between 1986 and 2014 was used for the study and were sourced from Central Bank of Nigeria (CBN) Statistical Bulletin. The stationary component of the variables was extracted using the Hodrick-Prescott (HP) and Band-Pass (BP) filter and then analyzed. The paper found out that all the macroeconomic variables were countercyclical and contemporaneously related to real gross domestic product, except for oil price and inflation where the filters produced mixed results of countercyclical and procyclical relationship with economic growth in Nigeria. The paper suggests effective and better management of macroeconomic variables if the desired level of growth is to be achieved.